The Perceptions of Parents and Teachers about the Classroom Environment and Morality - Salahuddin, Dr.Afsheen (Journal of Arts & Social Sciences, 2020)
The basic objective of this study was to explore the issues of morality in the classroom environment and to look for the ways to teach moral values to the students during their classes. This small scale study has tried to provide some solutions to this issue.  The present study has adopted a qualitative paradigm for the in-depth analyses of the issues regarding morality and classroom education. The study includes semi structured interviews taken from ten parents whose children are studying at the university level. Moreover ten university teachers were also interviewed to know about their views regarding the issue of how to teach moral values to the students in the classroom setting along with teaching. The interviewees were chosen through purposive sampling technique.  The interviews were semi structured so that real views of the teachers and parents could be explored and also to make them feel relaxed. The interview consisted of five open ended questions. The interviews were recorded and later transcribed and then they were analysed by utilising the thematic analysis technique. The major themes which emerged after the analysis were that first of all, teacher should be a role model practicing the moral values himself/herself. Another theme was bridging the gap between parents and children, also enhancing friendliness among the teachers and their students so that students could be taught how to observe certain ethics and values in the classroom settings in an informal way like showing some videos or discussing some news which highlight some moral issues. Another theme was to develop a model based on moral education which should be incorporated into the curriculum of the educational institutes. The study provided some effective solutions which if incorporated in the classroom teaching can be helpful in solving the issue of morality among the students.